2021
DOI: 10.46568/bios.v2i2.55
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID19-affected Mental Health with Menstrual Abnormalities among University Students: A cross sectional study from Pakistan

Abstract: Introduction: Mental health is crucial for wellbeing. COVID-19 pandemic has caused mental health problems. In this study it was hypothesized that COVID19 related mental health disturbances may have impacted the menstrual health. Objective of this study was to evaluate the impact of COVID-19 affected mental health on the menstrual health of university students. Methods: A cross sectional study was conducted at University of Sindh, Jamshoro between July to August 2021 during fourth wave. A pre-tested questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Medina-Perucha et al 15 found 7.2% of their respondents experienced an increase in bleeding. This finding was in line with a study by Samo et al 13 which found that 15% of the respondents experienced heavy bleeding during the COVID-19 pandemic, and also in line with the research by Phelan et al 11 who also mentioned that 28% of the respondents had menstruation for more than eight days. Higher percentage was found on a study by Maher et al 12 which stated that 50% of their respondents felt that their menstrual volume during the pandemic had also increased.…”
Section: Menorrhagiasupporting
confidence: 92%
See 3 more Smart Citations
“…Medina-Perucha et al 15 found 7.2% of their respondents experienced an increase in bleeding. This finding was in line with a study by Samo et al 13 which found that 15% of the respondents experienced heavy bleeding during the COVID-19 pandemic, and also in line with the research by Phelan et al 11 who also mentioned that 28% of the respondents had menstruation for more than eight days. Higher percentage was found on a study by Maher et al 12 which stated that 50% of their respondents felt that their menstrual volume during the pandemic had also increased.…”
Section: Menorrhagiasupporting
confidence: 92%
“…Research conducted by Samo et al also found that 16% of the respondents experienced amenorrhea during the pandemic. [13][14][15][16][17][18][19][20] Higher percentage were found in a study by Garcia de Leon et al 21 , which found that 23.7% of their respondents, specifically 13.1% of their under 40s respondent having fewer periods than before.…”
Section: Amenorrheamentioning
confidence: 79%
See 2 more Smart Citations
“…In a study conducted in Mumbai, India, the results showed that more than half (78%) of the 155 respondents observed alterations in their menstrual periods (32). In another study applied in Pakistan, COVID-19 has impacted 59.75% of study participants' mental health (33). Moreover, in a study that was among students of the Faculty of Health Sciences during COVID-19, out of 500 students, 73% had severe PMS (34).…”
Section: The Impact Of Covid-19 On the Menstrual Cycle And Premenstru...mentioning
confidence: 99%